SISTEM INFORMASI KOPERASI PETANI GUNA PENINGKATAN PEREKONOMIAN DI DESA CILEMPUYANG - Kesuma, Chandra (Sekolah Tinggi Manajemen Informatika dan Komputer Jayakarta, 2025)
Farmer cooperatives in Cilempuyang Village have a strategic role in supporting the improvement of the economy of the village community. However, manual cooperative management often faces challenges such as lack of transparency, operational efficiency, and difficulties in financial records. This cooperative also provides various agricultural needs that can be purchased in installments and can provide loans and capital storage. However, officers still have difficulties in managing goods data and have to come directly to the cooperative for their members. This research aims to design and develop a web-based farmer cooperative information system that can improve the efficiency of cooperative management, speed up the transaction process, and provide accurate and transparent financial reports. This system provides member management features, recording of crop and loan transactions, as well as automatic financial reports that can be accessed in real-time by administrators and members. The system development methodology uses the waterfall method which consists of the stages of needs analysis, design, implementation, testing, and maintenance. With the implementation of this system, it is hoped that farmer cooperatives can become a driving force for a more independent and sustainable village economy.